Pulsed laser scan methodology for single event effect (SEE) qualification - Chua, Chung Tah (2019)
This thesis addresses the need for alternative methods of single event effect (SEE) radiation testing in a period when microelectronic technology nodes are scaling to ever smaller dimensions. This results in increasingly complex devices and compels radiation test engineers to demand radiation test techniques which are capable of providing more information (both spatially and temporally) as compared to conventional broad beam heavy ion radiation test. Moreover, reliability and lifetime of advanced microelectronic devices are getting lower and thus, this thesis aims to study the influence of device ageing on its SEE radiation response. These issues are further complicated by demands for efficient radiation test methods to cope with the industry-wide shift towards the use of large amount of commercially-off-the-shelf (COTS) components which are not manufactured with radiation hardness and high reliability as primary priorities.